2020
DOI: 10.1016/j.drugpo.2019.102642
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstance use in rural West Virginia: Associations between latent classes of drug use, overdose, and take-home naloxone

Abstract: Background.-Rural communities in the United States have been disproportionately affected by the opioid crisis. Little research has explored the relationship between polysubstance use and overdose experiences among people who inject drugs (PWID) in rural communities. We sought to identify classes of polysubstance drug use among rural PWID and evaluate the associations between polysubstance drug use classes, recent overdose experiences, and receipt of take-home naloxone (THN).Methods.-We surveyed 420 PWID (June-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Although these behaviors often occur in tandem, few have employed latent class analysis (LCA) to examine the complex patterns of polysubstance use among women who exchange sex [ 27 , 34 , 35 , 36 ]. LCA has been used to understand patterns of polysubstance use of both injection and non-injection drugs among various populations, including adolescents [ 37 ], adults in urban and rural settings [ 38 , 39 , 40 , 41 , 42 , 43 ], and women living with HIV [ 26 ]. Classes of people who engage in polysubstance use have been shown to have a differential risk of poor health and Hepatitis C virus (HCV) [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these behaviors often occur in tandem, few have employed latent class analysis (LCA) to examine the complex patterns of polysubstance use among women who exchange sex [ 27 , 34 , 35 , 36 ]. LCA has been used to understand patterns of polysubstance use of both injection and non-injection drugs among various populations, including adolescents [ 37 ], adults in urban and rural settings [ 38 , 39 , 40 , 41 , 42 , 43 ], and women living with HIV [ 26 ]. Classes of people who engage in polysubstance use have been shown to have a differential risk of poor health and Hepatitis C virus (HCV) [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that patterns of substance use differ between urban and rural areas, with rural people being more likely than their urban counterparts to inject drugs and engage in polysubstance use. [13–15]. IDU‐associated consequences can be prevented through the implementation of syringe services programs (SSPs), which provide a myriad of services to PWID, such as access to sterile injection equipment and drug treatment referrals [1].…”
Section: Introductionmentioning
confidence: 99%
“…New guidelines governing naloxone distribution were issued by the West Virginia state legislature in 2015, which maintained naloxone as a prescription medication and mandated stringent reporting requirements not placed on other controlled substances [ 21 ]. A latent class analysis using data from 2018 found that polysubstance use among people who inject drugs in Cabell County was highly prevalent and was associated with both overdose and receiving take-home naloxone [ 22 ]. Needle and syringe programs (NSP) have expanded in Appalachia since 2013, with nine open in West Virginia in August of 2017, although access is limited in many counties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%